Opioids From Analgesic Use to Addiction - Almela Rojo, Pilar (IntechOpen, 2020)
Morphine and other opioids are potent analgesic drugs, but their use can lead to complications. Being familiar with the use of this kind of drug can make the difference between obtaining the expected benefit of applied therapy or magnifying the risks to intolerable levels for the patient. Therefore, it is essential for practitioners to achieve adequate training in the management of these drugs based on criteria endorsed by scientific evidence that allows the proper use of these drugs and guarantees the best professional practice every time. Written by expert authors in the field, the purpose of this book is to offer an overview of opioid drugs, from their therapeutic use to the consequences associated.